Kepemimpinan Kepala Madrasah dalam Meningkatkan Mutu Pendidik di Era Moderenisasi Digital - Saefrudin (Sosaintek: Jurnal Ilmu Sosial Sains dan Teknologi, 2024)
The digital modernization of education, which has a big influence on educational leadership, must be addressed wisely by policy makers in the educational environment. Of course, it must be equipped with skilled leadership so that it has implications for the quality of educators. The approach in this research is descriptive qualitative with a type of literature study, data obtained through various national and international journal references and research results that have relevance to what the author is doing. This research shows that the leadership of madrasah heads in the modern era of digitalization must of course be proficient and competent in reading the changes that occur due to skilled leadership, namely leadership that follows technological developments. Madrasah heads also play a role in improving the quality of educators, as well as several things that educators must do, namely the use of information technology, training, mentoring and guidance, developing discipline and regular supervision.